Effect of dietary inorganic copper on growth performance and hematological profile of Nile tilapia subjected to heat-induced stress - Damasceno, Flavia M. [UNESP]; Fleuri, Luciana Francisco [UNESP]; Sartori, Maria Márcia P. [UNESP]; Amorim, Renee Laufer [UNESP]; Pezzato, Luiz E. [UNESP]; da Silva, Rafael L. [UNESP]; Carvalho, Pedro L.P.F. [UNESP]; Barros, Margarida M. [UNESP] (Elsevier, 2016)
The effects of graded levels of dietary copper supplementation on the growth, hematological profile, ceruloplasmin activity, and resistance to high temperature stress of Nile tilapia (Oreochromis niloticus) were analyzed. A total of 240 fish (8.05±0.45g) were randomly distributed in 30 tanks (250L) and fed six diets containing graded levels of Cu2SO4·5H2O (0.0, 4.0, 6.0, 8.0, 1000 and 1500mgCu·kg-1 diet) for 120days. Growth performance as well as hematological, biochemical and histopathological parameters in the liver were analyzed. After the feeding period, the fish were subjected to heat/dissolved oxygen-induced stress (32°C/2.3mg·L-1) for three days, when the same hematological and biochemical parameters were evaluated. The toxicity of dietary copper supplementation impaired the growth performance (P<0.05) of fish fed 1000mgCu·kg-1 and 1500mgCu·kg-1 and influenced the hematological profile after the feeding period (P<0.05). The ceruloplasmin enzyme exhibited higher activity after heat stress. Histopathological changes in the fish liver were observed in all of the treatments, regardless of the dietary copper supplementation. Fish fed diets without copper supplementation showed the lowest value of iron in the liver, which differed significantly (P<0.05) from the levels in fish fed the highest copper supplementations. The highest levels of copper supplementation resulted in the highest values of copper concentration in the liver, whereas supplementation with 0-8mgcopper/kg diet did not change the copper concentrations in the liver. Therefore, considering the fish growth, health, ceruloplasmin activity and liver histopathology, it can be concluded that levels of available copper close to the required amount were sufficient to ensure the growth and health of Nile tilapia, even under the stress condition, whereas an excess of this mineral in the diet impaired the growth and health of this species. Statement of relevance: Copper is an essential micro mineral, and its requirement has been established for some fish species. However, there is a lack of information on the effects of dietary copper supplementation on fish subjected to stress. Therefore, it is important to understand how fish fed graded levels of copper respond under stress that is usual in fish farms. Thus, economic losses can be avoided.
Keywords: Histology; Mineral; Nutrition and health; Oreochromis niloticus; Toxicity